2023
DOI: 10.3390/su15010842
|View full text |Cite
|
Sign up to set email alerts
|

Bioremoval of Methylene Blue from Aqueous Solutions by Green Algae (Bracteacoccus sp.) Isolated from North Jordan: Optimization, Kinetic, and Isotherm Studies

Abstract: Algae provide an alternative, sustainable, and environmentally beneficial method of dyetreatment. In this study, algae were successfully used to remove methylene blue (MB) from aqueous solutions. The effects of several parameters, such as initial concentration of MB (5–25 mg L−1), algae dosage (0.02–0.1 g mL−1), temperature (4, 20, and 30 °C), and contact time (24, 48, 72 and 84 h), on MB removal were investigated. In addition, the characterization of MB before and after treatment was achieved using UV-spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…C i , C e , and C t are the initial, equilibrium, and time of OTC concentrations (mg·L −1 ), respectively. V is the OTC solution volume (L), and M is the weight of adsorbent (g) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…C i , C e , and C t are the initial, equilibrium, and time of OTC concentrations (mg·L −1 ), respectively. V is the OTC solution volume (L), and M is the weight of adsorbent (g) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…was isolated and morphologically characterized from water springs in Mafraq city in northern Jordan and applied for methylene blue bioremoval. 18 In addition, Chlorella sorokiniana isolated from Al-Fuheis wastewater treatment plant showed significant nephroprotective activity in mice as described by Al-Halaseh et al 9 Moreover, microalgae have been isolated from the Dead Sea as reported by AbuSara et al 19 The authors identified Dunaliella sp. on the southeastern shores, and its B-carotene production increased when the growth conditions were optimized to 40 mg L -1 nitrogen as NaNO3, 25 mg L -1 sulfate as MgSO 4 , and light intensity of 200 µmol s -1 m -2 .…”
Section: Introductionmentioning
confidence: 91%
“…The immobilization of the Bracteacoccus sp. was accomplished based on the procedure described in a previous study [19]. In detail, a solution of sodium alginate (3%) was well mixed with a suspension of the Bracteacoccus sp.…”
Section: Immobilization Of the Bracteacoccus Spmentioning
confidence: 99%
“…Therefore, the decolorization of the MO solution by the Bracteacoccus sp. could occur as a result of both degradation and sorption processes (binding of the dye molecules by functional groups such as hydroxyl, carboxylate, phosphate, amino, and sulfate groups on the algal surface) [19].…”
Section: Uv-vis Analysismentioning
confidence: 99%